2022
DOI: 10.3390/children9081174
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Physical Exercise as Approach to Prevention and Reversion of Non-Alcoholic Fatty Liver Disease in Children and Adolescents with Obesity

Abstract: Non-alcoholic fatty liver disease (NAFLD) is an important health concern during childhood; indeed, it is the most frequent cause of chronic liver diseases in obese children. No valid pharmacological therapies for children affected by this condition are available, and the recommended treatment is lifestyle modification, usually including nutrition and exercise interventions. In this narrative review, we summarized up-to-date information on the benefits of physical exercise on NAFLD in children and adolescents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 168 publications
0
4
1
Order By: Relevance
“…In the present cohort, the prevalence of ultrasound-measured advanced liver stiffness in adolescence is <1%, and transient elastography-measured severe liver steatosis is ~10% in young adulthood. Inflammation partly mediated the association of ST with severe liver steatosis and cirrhosis 28 , while triglyceride and insulin resistance had no significant mediating effect in contrast with previous evidence 3,4,21,28 . Although ST may independently increase fat mass, fat mass suppressed the relationship between ST and severe liver steatosis and fibrosis, suggesting that fat mass in an apparently healthy cohort may not be deleterious to liver health, akin to a report on vascular health 12,14,29 .…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In the present cohort, the prevalence of ultrasound-measured advanced liver stiffness in adolescence is <1%, and transient elastography-measured severe liver steatosis is ~10% in young adulthood. Inflammation partly mediated the association of ST with severe liver steatosis and cirrhosis 28 , while triglyceride and insulin resistance had no significant mediating effect in contrast with previous evidence 3,4,21,28 . Although ST may independently increase fat mass, fat mass suppressed the relationship between ST and severe liver steatosis and fibrosis, suggesting that fat mass in an apparently healthy cohort may not be deleterious to liver health, akin to a report on vascular health 12,14,29 .…”
Section: Discussioncontrasting
confidence: 83%
“…In the largest and longest follow-up study to date, accelerometermeasured cumulative ST, LPA and MVPA from childhood through young adulthood were independently but differently related to the various liver indices and enzymes during growth from adolescence to There is a scarcity of longitudinal studies in children and adolescents that have examined the relationships between accelerometer-measured ST and liver steatosis and fibrosis 3,11,20,21 . A recent cross-sectional study of 667 middle-aged adults from the Netherlands with a MASLD prevalence of 34.3% reported that accelerometer-measured ST was not associated with higher odds of ultrasound-assessed liver steatosis after full adjustment for cardiometabolic factors 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAFLD represents a spectrum of progressive liver damage that progressively evolves from mild fatty liver to severe fibrosis. In the initial stages, NAFLD can be reversible, so accurate screening of subjects with risk factors is mandatory to avoid irreversible damages [ 30 ]. NAFLD is an important health issue in PCOS subjects, but to date is still little studied, especially in adolescents.…”
Section: Discussionmentioning
confidence: 99%